Work From Coffee Shop Trend: The Effect of Customer Interest on Customer Satisfaction and E-WOM Based on AIDA MODEL - Desy Oktaviani,; Keni Kaniawati,; Andhi Sukma, (Technium Business and Management, 2024)
In facing intense competition in the coffee shop industry in Bandung City, effective marketing strategies are crucial to capture attention and retain customers. This research aims to elucidate the impact of customer interest (using the AIDA approach) on customer satisfaction and e-WOM in the context of coffee shop selection for digital nomads in Bandung. The study uses a descriptive quantitative approach with 105 digital nomads in Bandung, and data processing is conducted using the SEM-PLS method. The research confirms that customer interest, specifically in the attention and action stages, significantly influences customer satisfaction. Furthermore, customer satisfaction proves to have a significant effect on e-WOM and serves as a partial mediator in the relationship between customer interest and e-WOM.